Electrodeposition and Anti-corrosive Properties of Polypyrrole Coatings on Stainless Steel - Rm. Meyyappan, A. Subathira and (Recent Research in Science and Technology, 2010)
Electrochemical deposition of polypyrrole coatings on stainless steel was carried out by the constant potential technique. This study will provide a better understanding of the corrosion protection mechanism of the polypyrrole coating. The structure of the coating was determined by using Reflection Absorption Infrared Spectroscopy (RAIR). The RAIR peaks ratios of the characteristic peaks were used to monitor the changes in the structure of polymer with respect to the process parameters. The change in corrosion current with process parameter was correlated with the extent of oxidation of the polymer. The mean roughness, rms roughness and the 3-D morphology of the coatings obtained from Atomic Force Microscopy (AFM) were used to correlate the surface energy changes of the coatings.